21ST CENTURY STEM EDUCATION: AN INCREASE IN MATHEMATICAL CRITICAL THINKING SKILLS AND GENDER - Suherman Suherman; Komarudin Komarudin; Revani Husain Setiawan (Raheema, 2022)
Enhancing the mathematical critical thinking ability in the 21st century is STEM learning. The research aims to see the mathematical skills of critical thinking between genders using STEM learning. The research method uses a quasi-experiment design 2 x 2 factorial design designs with a simple random sampling technique. Data collection techniques use a test method to see the results of the mathematical critical thinking skills of learners. Test analysis is conducted with the normality test and homogeneity testing, and the hypothesis of using two paths Anava. The research results are: (1) There are differences of STEM and conventional learning to the mathematical critical thinking skills as well as the use of STEM learning more effectively than conventional (2) there is a difference in the results of the mathematical critical thinking ability between male and female learners and the ability of the critical thinking skills of female learners to be higher than men.